ISLAMIC ELITES’ PERCEPTIONS OF MUSLIM LIYAN AND THEIR IMPACT ON RELIGIOUS MODERATION IN ISLAMIC EDUCATION - Fathiyaturrahmah; Widodo, Ari Dwi; Khair, Najibul (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study examines how Islamic elites in Jember Regency perceive Muslim Liyan (other Muslims) and how these perceptions influence the development of religious moderation within Islamic education. Using a qualitative phenomenological design, the research explores the subjective meanings underlying intra-Islamic differences through in-depth interviews, participatory observations, and document analysis involving kiai, organizational leaders, and influential preachers. Findings reveal three main typologies of perception: (1) mainstream orthodoxy that prioritizes doctrinal purity, (2) conditional tolerance that accepts diversity within certain boundaries, and (3) rigid exclusivism that rejects the legitimacy of differing groups. These perceptions are shaped by religious educational backgrounds, institutional interests, historical conflicts, and media-driven identity narratives. The study shows that inclusive elite perspectives support the cultivation of religious moderation in Islamic educational institutions, whereas exclusive views tend to foster polarizing attitudes among learners. This research contributes to the discourse on intra-religious exclusivism and offers practical implications for strengthening moderation-oriented curricula, teacher training, and dialogical learning environments within Islamic education. Penelitian ini mengkaji bagaimana elit Islam di Kabupaten Jember memandang Muslim Liyan (Muslim lainnya) serta bagaimana konstruksi pandangan tersebut memengaruhi pengembangan moderasi beragama dalam pendidikan Islam. Dengan menggunakan pendekatan kualitatif berdesain fenomenologis, penelitian menggali makna subjektif perbedaan intraumat Islam melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen terhadap kiai, pimpinan organisasi keagamaan, dan da’i berpengaruh. Temuan menunjukkan tiga tipologi utama persepsi: (1) ortodoksi arus utama yang menekankan kemurnian ajaran, (2) toleransi bersyarat yang menerima keberagaman dalam batas tertentu, dan (3) eksklusivisme keras yang menolak legitimasi kelompok berbeda. Pola tersebut dibentuk oleh latar pendidikan keagamaan, kepentingan institusional, sejarah konflik, dan pengaruh media. Penelitian ini menunjukkan bahwa sikap elit yang inklusif dapat memperkuat moderasi beragama di lembaga pendidikan Islam, sedangkan pandangan eksklusif berpotensi menumbuhkan sikap polarisatif pada peserta didik. Penelitian ini memberikan kontribusi bagi kajian eksklusivisme intraagama serta implikasi praktis bagi penguatan kurikulum moderasi, pelatihan guru, dan pembelajaran dialogis dalam pendidikan Islam.